Design of A Cassava Chatting Machine Using A Stem Approach - Eidelweis Dewi Jannati Eidelweis (Papanda Journal of Mathematics and Science Research, 2023)
ABSTRACT Designing a cassava chopping machine using a STEM (Science, Technology, Engineering, and Mathematics) approach is development research. Researchers developed a machine that previously used a manual pusher. In this machine, the pusher part uses a Belt Conveyor. This research method uses a STEM approach because in designing this machine the stages of observation, thinking and design are used. Design a cassava chopping machine using a STEM approach, get test results using Solidworks 2022 software and it is known that in the simulation analysis it shows stress with a stress value at F1 of 0.0027 N/mm2, at F2 of 0.0049 N/mm2, max displacement of 1.128e- 02mm, and a safety factor of 5.3 in the frame construction of the cassava chopper machine.